Hypothalamic obesity in children: pathophysiology to clinical management - BEREKET, ABDULLAH; HALİLOĞLU, BELMA (WALTER DE GRUYTER GMBH, 2015)
Hypothalamic obesity (HyOb) is a complex neuroendocrine disorder caused by damage to the hypothalamus, which results in disruption of energy regulation. The key hypothalamic areas of energy regulation are the ARC (arcuate nucleus), the VMH (ventromedial hypothalamus), the PVN (paraventriculer nuclei) and the LHA (lateral hypothalamic area). These pathways can be disrupted mechanically by hypothalamic tumors, neurosurgery, inflammatory disorders, radiotherapy and trauma or functionally as such seen in genetic diseases. Rapid weight gain and severe obesity are the most striking features of HyOb and caused by hyperphagia, reduced basal metabolic rate (BMR) and decreased physical activity. HyOb is usually unresponsive to diet and exercise. Although, GLP-1 and its anologs seem to be a new agent, there is still no curative treatment. Thus, prevention is of prime importance and the clinicians should be alert and vigilant in patients at risk for development of HyOb.
Keywords: children; craniopharygioma; hypothalamus; obesity; PRADER-WILLI-SYNDROME; INCREASED DAYTIME SLEEPINESS; GASTRIC BYPASS-SURGERY; EARLY-ONSET OBESITY; BODY-MASS INDEX; CHILDHOOD CRANIOPHARYNGIOMA; FOOD-INTAKE; LEPTIN RECEPTOR; ADIPOSE-TISSUE; RISK-FACTORS